PENGARUH KREDIBILITAS AGEN ASURANSI TERHADAP SIKAP NASABAH DALAM MEMBELI POLIS (Analisis Regresi mengenai keterpercayaan, keahlian dan daya tarik agen asuransi terhadap sikap pemilik asuransi di Kota Sukabumi) - Witanti Prihatiningsih; Fitria Ayuningtyas (Avant Garde, 2017)
Companies must have their own criteria for their sales agents, start from how tospeak in front of potential customers, personal appearance and knowledge aboutthe products and the company itself. The credibility of sales or marketing agentswill make their companies have a good reputation. Insurance agents also trainedby company to introduce the products until someone willing to buy the productsand become their loyal customer. This research aims to determine whether thereis any significant impact of insurance agent’s credibility to customer’s attitude inbuying a policy. The long-term results of the research can be used ascommunication competence for agents to persuade potential customers, whoprobably initially not interest to buy the products, became a loyal customer. Thisresearch is causal quantitative research. This research used regression analysisto determine the impact of insurance agent’s credibility to customer’s attitude inbuying policy. The data collection techniques used questionnaires that distributedto the respondent. The respondent of this research were people who haveinsurance in the city of Sukabumi, West Java. The sampling technique in thisresearch was purposive sampling. The theory that used in this research wassource credibility. The results of this research indicate that trustworthiness,expertise, and attractiveness of insurance agents have a significant impact tocustomer’s attitude in buying a policy. From the three components, the mostimportant thing is the expertise. The expertise of insurance agent has a highestscore compare with trustworthiness and attractiveness of insurance agent.